Physiological Basis of Preparation of the Child to Interact With the Surrounding World - Ihor Roshchin (Pedagogical Discourse, 2015)
In the article the author made an analysis of the scientific basis of the child’s interaction with the outside world. In summary, the interaction of the child with the environment, that is, his knowledge, is due to sensation and perception. The process of training and education of children in modern conditions of development has been examined.Characterized by the concept of «feeling» – a mental reflection of the properties of reality, that emerges and functions in the process of life. This is the cognitive activities through which the child receives basic information about the environment and the state of his body.A more complicated process is the perception – a reflection of objects, phenomena, processes, and the totality of their properties in their entirety with the direct impact of these objects and phenomena related to the senses. Perception is closely associated with motor activity, emotional experiences, various thought processes.In order to develop the senses, the interaction of the child with the world, that is in the process of cognition, should pay attention to such things as the perception of a holistic object, creating a general impression of him, the allocation of the main parts of the subject, the definition of their properties, the determination of the spatial distribution of some parts respect.Thus, if the preparation of the child for responsible interaction with the environment to build in that order, the study of objects of the world will be holistic and generalized. Moreover, the mastery of his own body, space activities, language and sensory standards, submission to the will of their own time – all of this will be targeted using the calculated and logically aligned loads analyzers.